Vacuolar nitrate efflux requires multiple functional redundant nitrate transporter in Arabidopsis thaliana - Lu, Yu-Ting; Liu, De-Fen; Wen, Ting-Ting; Fang, Zi-Jun; Chen, Si-Ying; Li, Hui; Gong, Ji-Ming (Frontiers in Plant Science, 2022)
Nitrate in plants is preferentially stored in vacuoles, however, how vacuolar nitrate is reallocated and to which biological process(es) it might contribute remain largely elusive. In this study, we functionally characterized three nitrate transporters NPF5.10, NPF5.14, and NPF8.5 that are tonoplast-localized. Ectopic expression in Xenopus laevis oocytes revealed that they mediate low-affinity nitrate transport. Histochemical analysis showed that these transporters were expressed preferentially in pericycle and xylem parenchyma cells. NPF5.10, NPF5.14, and NPF8.5 overexpression significantly decreased vacuolar nitrate contents and nitrate accumulation in Arabidopsis shoots. Further analysis showed that the sextuple mutant (npf5.10 npf5.14 npf8.5 npf5.11 npf5.12 npf5.16) had a higher 15NO3-uptake rate than the wild type Col-0, but no significant difference was observed for nitrate accumulation between them. The septuple mutant (npf5.11 npf5.12 npf5.16 npf5.10 npf5.14 npf8.5 clca) generated by using CRISPR/Cas9 showed essentially decreased nitrate reallocation compared to wild type when exposed to nitrate starvation, though no further decrease was observed when compared to clca. Notably, NPF5.10, NPF5.14, NPF8.5 as well as NPF5.11, NPF5.12 and NPF5.16 were consistently induced by mannitol, and more nitrate was detected in the sextuple mutant than in the wild type after mannitol treatment. These observations suggest that vacuolar nitrate efflux is regulated by several functional redundant nitrate transporters, and the reallocation might contribute to osmotic stress response other than mineral nutrition.